DEVELOPING A COMPUTER GAME ENTITLED THE CITY OF ENGLISH AS A MEDIUM IN TEACHING VOCABULARY TO TENTH GRADERS (RETAIN, 2014)
DEVELOPING A COMPUTER GAME ENTITLED THE CITY OF ENGLISH AS A MEDIUM IN TEACHING VOCABULARY TO TENTH GRADERS Fitria Aftinia English Department, Faculty of Languages and Arts, State University of Surabaya niafa13@gmail.com Ririn Pusparini, S.Pd., M.Pd. English Department, Faculty of Languages and Arts, State University of Surabaya rrn.puspa@gmail.com ABSTRAK Penelitian ini bertujuan untuk mengembangkan permainan berbasis komputer sebagai media pembelajaran vocabulary dalam teks deskriptif untuk siswa SMA kelas X dan diberi nama The City of English. Penelitian ini menggunakan langkah-langkah Penelitian dan Pengembangan (R & D) yang dimodifikasi yang meliputi kajian pustaka, survei lapangan, desain produk, validasi desain, revisi desain, dan uji coba. Instrumen yang digunakan yakni lembar validasi, lembar observasi, lembar angket dan lembar wawancara. Data yang telah didapat kemudian dikumpulkan dan dianalisis dengan cara persentase. Ada tujuh kriteria yang digunakan dalam menentukan kelayakan sebagai media pembelajaran. Hasil penelitian menunjukkan bahwa data validasi, observasi, angket dan wawancara yang diperoleh telah memenuhi kriteria tersebut. Sehingga secara keseluruhan dapat disimpulkan bahwa permainan yang dikembangkan memenuhi sebagai media pembelajaran yang baik dan efektif. Kata Kunci: Permainan The City of English, Vocabulary, Kelas Sepuluh. ABSTRACT This research aims to develop a computer game entitled The City of English as a medium in teaching vocabulary in descriptive text to tenth graders. In this research, modified steps of Research and Development (R&D) were used. Those are literature review, field survey, product design, design validation, design revision, and field testing. The research instruments are validation form, observation form, questionnaire form, and interview form. All data gathered were analyzed and resulted in percentage. There were seven criteria used in determining the expediency of the medium. The result showed that the data of validation, observation, questionnaire, and interview obtained met those criteria. Overall, it can be concluded that the game developed is appropriate as a good and effective instructional medium. Keywords: The City of English Game, Vocabulary, Tenth Graders. INTRODUCTION Based on Undang-Undang Number 20/2003 about National Education System, curriculum is a set of plans and setting of the objectives, content, and teaching materials as well as the methods used to guide the implementation of learning activities to achieve specific educational objectives. Curriculum 2013 which is already inaugurated aims to prepare Indonesia people in order to have the ability to live as a person and a faithful, productive, creative, innovative, and affective citizen. It is also expected that people especially students are able to contribute to society, nation, state, and civilization of the world. Concerning the curriculum 2013, the structure of secondary education curriculum consists of a number of subjects (compulsory and elective subjects), time allocation (beban belajar), and school calendars. English becomes one of compulsory subjects and elective subjects. The purpose of English subject itself cannot be separated from the function and purpose of national education. The purpose of English subject is to develop the potential of students in order to have interpersonal, transactional, and functional competence, by using oral and written communicative action, by using a variety of English texts at the level of functional and informational. According to curriculum 2013, English is given to students starting from the first grade of junior high school. Relating to the types of learners, Sugar and Sugar (2002) states that learning types can be expressed into two. They are internal and external styles. In making a product or solution, internal learners prefer working alone. They tend to find the solutions in their heads before bringing up an answer (Sugar & Sugar, 2002). At the same time, external learners are very social and evolve on group interaction and collaboration. Games are surely helpful in engaging those two types of learner. As Sugar and Sugar (2002) say, games help encouraging internal learners in providing the best answers and also serve an opportunity for external learners in testing their leadership skills out. In basic competence of English as compulsory subject for tenth graders, in curriculum 2013, it is stated that students are expected to comprehend the meanings of descriptive text about people, tourism objects, and well-known historic buildings both in spoken and written form. In fact, according to questionnaire that the writer has shared to thirty five students of senior high school in Surabaya, twenty one students admit that they find it difficult in understanding text in English lesson. The reason is they do not know the meaning of vocabulary, in other words, it is because they lack of vocabulary. It is understandable because vocabulary and reading are related closely (Constantinescu, 2007). Looking back at standar isi of the previous curriculum, there are some principles of curriculum implementation. One of them is learners should receive qualified education, as well as an opportunity to express themselves freely, dynamically and delightfully. While in curriculum 2013, the improvement of some mindsets is developed. One of them is the change of one-way learning into interactive learning. In order to make an interactive learning and give students opportunity to express themselves delightfully, teacher can use media. There are some categories of media such as visual, audio, audio visual, and multimedia. Presently, multimedia are often be used in various fields including in education. A principle of curriculum implementation in standar isi 2006 says that the curriculum is implemented by using multi-strategy and multimedia approach. It is actually same as the learning patterns which are stated in regulation of Education and Culture Minister Number 69 Year 2013 about basic structure and curriculum framework of high school/Madrasah Aliyah. Another improvement of mindsets stated in curriculum 2013 is the change of learning patterns from a single tool to multimedia-based learning. Therefore, using multimedia in language classroom clearly supports curriculum implementation. There are many examples of multimedia and one of them is computer games. Using games in language teaching and learning is supported by Prensky (2003) who states that there is enormous potential for learning in gaming. In order to meet particular instructional needs, some instructional games can be readily modified (Heinich, Molenda, Russell, & Smaldino, 1999). According to Sugar and Sugar (2002), games can assist educators to maximize the learning potential of each student. In fact, although there are so many educational games in the form of computer games which are available, schools in Indonesia seldom use it in language classroom. Knowing that almost all schools in big cities like Surabaya already have computers for each student, it is not impossible to make use the facility for teaching and learning activity especially for English subject. In the computer game which is developed, students as players must follow the plot of story that the game provides. In the game, students meet some characters who lead them to a case that must be solved. To solve the case, students are given three descriptive texts and some questions related. The story is written in English and students can know the translation of some words in Bahasa Indonesia by using cursor. The questions given are related to vocabulary in descriptive text. The correct answers will be showed up after students answer all questions for each text. In the previous research conducted by Pamula (2012), a computer game named Snakes and Ladders was produced. However, the game is intended for second graders of elementary school. Recently, it is not easy to find the proper games that meet the curriculum. Knowing there is a gap between the expectations in curriculum and the facts, this research will be beneficial. The focus of this research is developing an educational game for computer named The City of English. The game which is developed functions as medium in teaching vocabulary to tenth graders. Based on the explanation above, this research was intended to develop a computer game entitled The City of English as a medium in teaching vocabulary to tenth graders and to know students’ responses toward the game. It is hoped that this research would give benefits for students as a medium to learn vocabulary in descriptive text and for English teachers as an alternative medium in teaching vocabulary. METHODOLOGY This research used Research and Development (R&D). According to Gay (1987), developing effective products for use in schools is the major aim of R & D efforts. The researcher developed a product which was a computer game named The City of English as a medium in teaching and learning vocabulary. Borg and Gall (1983) state some steps of R & D and this research used modified steps based on the researcher’s need. Those steps are divided into two stages. The first is preliminary stage which consists of literature review and field survey. Literature review includes analyzing learners, stating the objective, selecting methods, selecting media, and selecting materials, while field survey includes teachers’ and students’ condition, media, and school environment. In analyzing students’ need, questionnaire was shared to thirty five students of tenth grade in SMA Muhammadiyah 2 Surabaya. The second is development stage which comprises product design, design validation, design revision, field testing, and report. The researcher used students in testing out the medium developed. They were students in one class of tenth grade in SMA Muhammadiyah 2 Surabaya which the class was decided by using simple random sampling. Since the researcher intended to apply the game in international class, every international class of tenth grade in SMA Muhammadiyah 2 Surabaya had equal possibility to be chosen as sample. In this sample technique, “the sample is unbiased and the inferences are most generalizable amongst all probability sampling techniques” (Bhattacherjee, 2012). Finally, X MIA 2 was chosen as sample. The target of research was game developed and the sources were data from experts, students, and observers. This research used some instruments; those are validation form, observation checklist, questionnaire, and interview. The validation form was used to assess the game developed based on the theories. The theories are: (1) Instructional media must be compatible with learning objective (Indriana, 2011), (2) Instructional media must be compatible with instructional content (Indriana, 2011), (3) The materials in media are valid (Erickson & Curl, 1972), (4) One criterion of instructional media is the technical quality (Walker & Hess, 1984). The validation form contains 4 scales; strongly disagree, disagree, agree, and strongly agree. The persons who filled the validation form were English teachers as experts and practitioners. Then the game was revised based on experts’ suggestions by considering the learning objectives which should be achieved. After being revised, the game was field tested. The observation was used to know students’ activities during the teaching and learning process by using game developed. Observation sheets were filled in by observers and they took notes activities happened during field testing too. Data of observation were also used to know whether the game developed was suitable with the theory from Fenrich (1997), that was an effective game should involve students actively in learning. After applying the game developed, questionnaire was shared to students. The questionnaire contains 4 scales; strongly disagree, disagree, agree, and strongly agree. It was used to know students’ responses and whether the game developed was suitable with theories; (1) Instructional media are attractive (Erickson & Curl, 1972), (2) Games can be fun ways to learn (Fenrich, 1997), (3) An effective game should challenge students (Fenrich, 1997). Interview was conducted to nine students as representatives of the class; three students with high proficiency in English, three students with middle proficiency in English, and others with low proficiency in English. It was used to match the answers on questionnaire. The data of validation and questionnaire were analyzed by using formula stated below. The percentage = SUM is total of score obtained and highest score is four times the total number of respondents. Data of observation were analyzed by using formula stated below. Percentage = The data analysis resulted in percentage and the percentage was interpreted in criteria. Table 1 The Criteria of Score Interpretation The Percentage Criteria 0% - 20% Very weak 21% - 40% Weak 41% - 60 % Enough 61% - 80% Strong 81% - 100% Very strong (Riduwan, 2010) If the answer compatibility between questionnaire and interview is ≥ 60%, the result of questionnaire is considered appropriate. RESULTS AND DISCUSSIONS The game was developed in two stages; those are preliminary stage and development stage. In preliminary stage, it was known that learners were adolescents and based on their development stage the game developed was suitable with them. The condition of school, teacher, and students support the game developed. In development stage, the data of validation showed that every indicator reached at least strong criterion. It means that the game developed fulfils the criteria which say that instructional media must be compatible with learning objective and instructional content, the materials in media are valid, and the technical quality must be considered in instructional media (Indriana, 2011; Erickson & Curl, 1972; Walker & Hess, 1984). Since the experts gave some suggestions, the game was revised first before it was applied. However, not all suggestions were used to revise the game because the game developed should achieve learning objectives which had been determined. The first revision was about the character’s movement and the second revision was about score displayed on the game. Before Revision After Revision Figure 1 The Character’s Movement Before Revision After Revision Figure 2 The Display of Score The result of validation is briefly stated in the table below. Table 2 The Result of Validation by the Experts No. Indicators Result Percentage Criteria Expert 1 2 The medium is compatible with the learning objective. 4 3 87.5% Very strong The medium is suitable to be used for teaching vocabulary. 3 4 87.5% Very strong Synonyms and antonyms in the text displayed in the game are appropriate. 4 4 100% Very strong The instruction in the game is clear. 4 4 100% Very strong The display of words is suitable with background. 4 4 100% Very strong The appearance of picture is suitable with background. 4 4 100% Very strong The words in the medium are easy to be read. 4 4 100% Very strong The colours are attractive. 3 4 87.5% Very strong The display of text is attractive. 3 4 87.5% Very strong The pictures in the game are attractive. 3 3 75% Strong Average 92. 5% Very strong Students’ activities observed showed that more than sixteen students did not divert their attention from the medium (game) used, continued to play the game during the time provided, did the activity based on the instruction, expressed their happiness during the game, and wanted to continue playing although the time provided was up. However, eighteen students asked about the instruction in the beginning. This activity was observed just to know the clarity of the game developed. Although this only one indicator did not reach strong criteria, the result still showed that the game developed involved students actively in learning (Fenrich, 1997). The data got were shown in the table below. Table 3 The Result of Observation No. Aspects Number of Students Percentage Yes No Yes No 1. Students do not divert their attention from the medium (game) used. (No chatting with other friends). 18 3 86% 14% 2. Students continue to play the game during the time provided. (They do not do other activities like doing something with their cell phones.) 18 3 86% 14% 3. Students do not ask about the instruction or rules of the game to other students or teacher. 3 18 14% 86% 4. Students do the activity based on the instruction. 20 1 95% 5% 5. Students express their happiness (by smiling, laughing, etc.) during the game. 20 1 95% 5% 6. Students want to continue playing although the time provided is up. 17 4 81% 19% Questionnaire was shared to students after they played the game. According to the result of questionnaire, every indicator reached at least strong criterion. It means that the game developed is suitable with theories: Games can be fun ways to learn (Fenrich, 1997), the instructional media are attractive (Erickson & Curl, 1972), and an effective game has to challenge students (Fenrich, 1997). The data of questionnaire were shown in the table below. Table 4 The Result of Questionnaire No. Indicators Percentage Criteria 1. The game is interesting. 79% Strong 2. Students want to play it again. 75% Strong 3. The game is suitable with students’ interests. 69% Strong 4. Students like learning English if the game like this is used. 89% Very strong The Students’ Interest 78% Strong 5. The game design is very attractive. 74% Strong 6. The way to play the game is interesting. 76% Strong 7. The rules of the game are easy to be understood. 82% Very strong The Attractiveness of the Medium 77% Strong 8. Students do not want to fail in completing the mission on the game. 85% Very strong 9. Students want to play again if they fail to complete the game. 83% Very strong The Challenge Provided by the Medium 84% Very strong Average 79% Strong Data obtained from interview showed that more than 61% of students’ answers were the same as the answers on questionnaire. Therefore, the answers on questionnaire were considered appropriate. Finally, after all data got were analyzed, the results were reported. CONCLUSIONS AND SUGGESTIONS Conclusions From the result and discussion, it can be concluded that the game developed was developed in two stages. They were preliminary stage and development stage. In preliminary stage, literature review and field survey were conducted. From those two steps, it can be said that the game developed supports teachers’ and students’ condition, media, and school environment. In development stage, product design, design validation, design revision, and field testing were conducted. Those steps were done and the result was finally reported. These two stages result in a computer game as medium in teaching vocabulary for tenth graders. The students’ responses toward the game developed are good. All students stated that the rules of the game developed were easy to be understood and they liked learning English if the game like this was used. Students’ opinions were also got from the interview and the result showed positive responses. Overall, it can be said that the game developed fulfils seven criteria of effective and good instructional media. Those are: (1) Instructional media must be compatible with learning objective (Indriana, 2011), (2) Instructional media must be compatible with instructional content (Indriana, 2011), (3) The instructional media are attractive (Erickson & Curl, 1972), (4) The materials in media are valid (Erickson & Curl, 1972), (5) One criterion of instructional media is the technical quality (Walker & Hess, 1984), (6) An effective game has to challenge students and involve them actively in learning (Fenrich, 1997), (7) Games can be fun ways to learn (Fenrich, 1997). Suggestions Since the game entitled The City of English needs time for its preparation to be utilized in classroom, teacher must pay attention to computers or laptops available. They must be free from virus which can hinder the teaching and learning process. Teacher may also tell students that there will be exercises after playing the game so the students do not just click everything at random. It can avoid the weakness of educational games that is “some products show fancy displays, but do not teach” (Fenrich, 1997). For further development, the game could be given voice every time the sentence, monologue or dialogue, appears on the screen. It can train students’ listening skill and help them in speaking with correct pronunciation. Besides, in this research, the development of the game entitled The City of English was only tested in small scale so it needs further research to be utilized as the medium in bigger scale. REFERENCES Bhattacherjee, A. (2012). Social Science Research: Principles, Methods, and Practices Borg, W. R., & Gall, M. D. (1983). Educational Research: An Introduction (4 ed.). New York: Longman Inc. Constantinescu, A. I. (2007). Using Technology to Assist in Vocabulary Acquisition and Reading Comprehension. The Internet TESL Journal, XIII(2). Erickson, C. W. H., & Curl, D. H. (1972). Fundamentals of Teaching with Audiovisual Technology (2 ed.). New York: Macmillan Publishing Company Inc. Fenrich, P. (1997). Practical Guideliness for Creating Instructional: Multimedia Applications. Fort Worth: The Dryden Press, Harcourt Brace College Publishers. Gay, L. R. (1987). Educational Research: Competencies for Analysis and Application (3 ed.). Ohio: Merrill Publishing Company. Heinich, R., Molenda, M., Russell, J. D., & Smaldino, S. E. (1999). Instructional Media and Technologies for Learning (6 ed.). New Jersey: Prentice-Hall, Inc. Indriana, D. (2011). Ragam Alat Bantu Media Pengajaran. Jogjakarta: DIVA Press. Pamula, E. (2012). Modifying Conventional Snakes and Ladders Game into Computer Game as a Medium for Teaching Vocabulary to the Second Graders. Bachelor, Universitas Negeri Surabaya, Surabaya. Prensky, M. (2003). Digital game-based learning. ACM computers in entertainment, 1(1), 1-4. Riduwan. (2010). Skala Pengukuran Variabel-variabel Penelitian. Bandung: ALFABETA. Sugar, S., & Sugar, K. K. (2002). Primary Games: Experiental Learning Activities for Teaching Children K-8 (1 ed.). San Francisco: Jossey-Bass. Walker, D. F., & Hess, R. D. (1984). Instructional Software: Principle and Prespectives for Design and Use. California: Wadsworth, Inc.